Primeiro como tragédia: o humor crítico-negativo em Esperando Godot, de Samuel Beckett - Oliveira, Filipe Marinho de (2022)
This study addresses the topic of critical negative humour and establishes an analysis that relates Samuel Beckett’s play Waiting for Godot and Theodor Adorno's writings on aesthetics, literature, and the critique of enlightenment. Based on the understanding of aesthetics as a dimension with no immediate social determination, we inquire about the contributions that this play can offer to the discussion on the aesthetic dimension of critical negative thinking, as conceived by Adorno and Horkheimer. We find in the dialectical method and in Theodor Adorno’s Aesthetic theory foundations for analysis that allow us to affirm that humour in Beckett’s play reveals aspects that are essential for obtaining an understanding about the aesthetic dimension of critical negative thinking. The nothingness of the profoundly tragic humour in Vladimir and Estragon does not empty the constitutive enygma of the narrative once it is classified as a tragicomedy, although its singularity presents aspects that can deepen the discussions on the aesthetics of humour. Furthermore, Beckett’s work shows the contradictions of modern society’s development after Auschwitz, calling attention to the incompatibility of enlightened rationality in modern times. For that reason, Beckett’s clowns repeat the same act to exhaustion: they come from a world in which the remaining order is chaos, and they do not find any positive meaning in the metaphysical sense, although Vladimir and Estragon hope for a reconciliation with this humanistic ideal in order not to admit the failure of the enlightenment project under Godot’s character. Despite the critique on enlightened rationality, the possibility of a remaining philosophy calls attention as an effort to say the unspeakable. Such possibility is due to the potency of critical negative thinking enhanced by the idea of a non-identifying reason – a potential that shows up in Waiting for Godot’s critical negative humour.